2016
DOI: 10.4142/jvs.2016.17.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium vaccaeinduces a strong Th1 response that subsequently declines in C57BL/6 mice

Abstract: Mycobacterium (M.) vaccae is a fast-growing species of saprophytic bacteria that is widely distributed. To understand the host immune responses induced by M. vaccae isolated from bovine submaxillary lymph nodes, C57BL/6 mice were infected with reference strain M. vaccae Bacillus Calmette-Guérin (BCG) and isolated M. vaccae using intraperitoneal injections. Comparison of the bacterial replication and organ pathology between M. vaccae and M. vaccae BCG revealed that M. vaccae was more malignant than M. vaccae in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…The long-term, Treg-dependent protection from stress-induced exaggeration of spontaneous colitis and anxiety-like defensive behavioral responses in the CSC paradigm (measured 4 weeks after the final immunization with heat-killed M. vaccae NCTC 11659) are consistent with the long-term, Treg-dependent protection from allergic airway inflammation in a murine model of allergic asthma (Zuany-Amorim et al, 2002a,b). Finally, the time course of protective effects of M. vaccae NCTC 11659, in the context of spontaneous colitis and anxiety-like defensive behavioral responses (Reber et al, 2016b), are consistent with the time course of induction of Treg following infection of mice with a live strain of M. vaccae isolated from bovine submaxillary lymph nodes, in which CD4 + CD25 + Foxp3 + Treg are elevated within 1 week of infection, reach maximal levels 3 or 4 weeks following infection, and remain elevated until at least 8 weeks following infection (Zhang et al, 2016).…”
Section: Effects Of M Vaccae Nctc 11659 On the Host Brainstem Serotosupporting
confidence: 64%
“…The long-term, Treg-dependent protection from stress-induced exaggeration of spontaneous colitis and anxiety-like defensive behavioral responses in the CSC paradigm (measured 4 weeks after the final immunization with heat-killed M. vaccae NCTC 11659) are consistent with the long-term, Treg-dependent protection from allergic airway inflammation in a murine model of allergic asthma (Zuany-Amorim et al, 2002a,b). Finally, the time course of protective effects of M. vaccae NCTC 11659, in the context of spontaneous colitis and anxiety-like defensive behavioral responses (Reber et al, 2016b), are consistent with the time course of induction of Treg following infection of mice with a live strain of M. vaccae isolated from bovine submaxillary lymph nodes, in which CD4 + CD25 + Foxp3 + Treg are elevated within 1 week of infection, reach maximal levels 3 or 4 weeks following infection, and remain elevated until at least 8 weeks following infection (Zhang et al, 2016).…”
Section: Effects Of M Vaccae Nctc 11659 On the Host Brainstem Serotosupporting
confidence: 64%
“…In DAR‐901 clinical trials, where enhanced protection was observed compared with BCG, the amount of cytokine produced was no higher than in BCG vaccination 38 . Alternatively, a marked increase in the number of polyfunctional T cells has been attributed to the protective capacity of some Mtb vaccines candidates 9–11,43 …”
Section: Discussionmentioning
confidence: 99%
“…The poorly characterized mechanism of protection achieved through BCG vaccination in children, and the lack of natural sterilizing immunity following Mtb infection have hindered the identification of a correlate of protection, further complicating Mtb vaccine development. While there is no definitive correlate of protection, Mtb vaccines candidates have been postulated to elicit protection through mechanisms such as the development of peptide‐specific T CM (central memory) and T RM (resident memory) cells, 8 and induction of T cells that simultaneously produce tumor necrosis factor‐α (TNF‐α), interferon‐γ (IFNγ), interleukin (IL)‐2 and IL‐17 and combinations thereof 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…Par conséquent, M. vaccae pourrait protéger les souris contre l'infection par M. tuberculosis et améliorer l'immunité à médiation cellulaire innée et adaptative de la souris, suggérant que M. vaccae est un agent immunothérapeutique potentiel dans la tuberculose pulmonaire (Xu et al, 2009). Un constat similaire a été rapporté par l'étude menée par Zhang et al, 2016 montrant que des injections contenant M. vaccae tuée par la chaleur peut provoquer une augmentation des réponses de lymphocytes T régulateurs et T auxiliaires de type Th1, ce qui peut protéger l'hôte contre l'infection tuberculeuse (Zhang et al, 2016).…”
Section: -Tuberculoseunclassified